The Yeast V159N Actin Mutant Reveals Roles for Actin Dynamics In Vivo - Belmont, Lisa D. (The Rockefeller University Press, 1998)
Actin with a Val 159 to Asn mutation (V159N) forms actin filaments that depolymerize slowly because of a failure to undergo a conformational change after inorganic phosphate release. Here we demonstrate that expression of this actin results in reduced actin dynamics in vivo, and we make use of this property to study the roles of rapid actin filament turnover. Yeast strains expressing the V159N mutant (act1-159) as their only source of actin have larger cortical actin patches and more actin cables than wild-type yeast. Rapid actin dynamics are not essential for cortical actin patch motility or establishment of cell polarity. However, fluid phase endocytosis is defective in act1-159 strains. act1-159 is synthetically lethal with cofilin and profilin mutants, supporting the conclusion that mutations in all of these genes impair the polymerization/ depolymerization cycle. In contrast, act1-159 partially suppresses the temperature sensitivity of a tropomyosin mutant, and the loss of cytoplasmic cables seen in fimbrin, Mdm20p, and tropomyosin null mutants, suggesting filament stabilizing functions for these actin-binding proteins. Analysis of the cables in these double-mutant cells supports a role for fimbrin in organizing cytoplasmic cables and for Mdm20p and tropomyosin in excluding cofilin from the cables.